Information Provision of Management in Conditions of Digitization - Gerasymenko, S. S.; Нerasymenko, V. V. (Statistics of Ukraine, 2023)
With the growing competition, the rapidly developing technologies and the unstable economic conditions, enterprises have to face the objective of effective monitoring and analysis of the business performance. The ability of adaptation to changes, quick response on risks and timely updating of the strategies is key to success. By creating the adequate information support enterprises are allowed to not only survive in unstable conditions, but actively develop and take leading positions on the market. The article elaborates on to the problems which solutions would allow to match the processes involved in the design of information support for management with the conditions of global digitalization of economy and society, using Data Analysis approach. The contemporary world is witnessing rapid technological change that triggered digitalization in all walks of life. This process shows in the transition from paper documentation to the digital format, uses of information technologies in management and business operation. Digitalization has been radically changing the mode of management in organizations. Information support of management in the context of digitalization requires introduction of advanced technologies and effective use of information to achieve strategic goals. For successful management in the contemporary world, it is necessary to focus on improving information processes and ensuring their security, which are key factors of success in the digital era. In order to implement digital transformation into practice, it is necessary, first of all, to consider the relevant concepts, methods and tools. The introduction of innovative information technologies is a key factor in increasing competitiveness by creating an effective information base for business management.